Potential impacts of automated vehicles, electric vehicles, and shared mobility on sustainable urban mobility - Gortaire, Camila Andrade (2025)
The transportation sector presents a challenge for public policies, due to its negative externalities, which have economic, social, and environmental consequences. The topic of sustainable urban mobility has been widely researched to address these challenges, with many studies proposing actions to promote it. However, with the emergence of new forms of transport, such as automated vehicles (AVs), electric vehicles (EVs), and shared mobility, the sustainability of the urban mobility system may eventually become less aligned with reality. For this reason, this study investigates the relationships between urban mobility variables, aiming to detect, describe, and analyze the potential impacts of AVs, EVs, and shared mobility on sustainable urban mobility through qualitative system dynamics modeling. First, the main system variables and their interrelationships were identified. Then, based on a literature review, causal loop diagrams (CLDs) of the urban mobility system were created under different conditions: in its original state and after implementing AVs, EVs, and shared mobility. Results indicated that a non-linear paradigm of thinking provides a comprehensive framework to address urban mobility issues. Interpreting the CLDs from a sustainability perspective revealed that policies favoring a mode of transportation without considering indirect and long-term effects can undermine the sustainability of the system. Furthermore, the resulting qualitative models are useful tools because they facilitate the visualization of direct and indirect consequences of implementing not only technologies but also public policies. Lastly, the study presented policies and actions that contribute to increasing the sustainability of the urban mobility system.